Models of sports student exchange and the role of their support systems - Fatona Suraya; Tandiyo Rahayu; Rebecca Alcuizar (UIR Press, 2021)
Establishing student exchange programs is one way for sports science faculty to support the University to be a world-class university. For several years the faculty has been hosting several batches of a sports students exchange (SSE) program that gains interest and benefits for the students and the institution; however, limited studies have been conducted to present information about the program and its support system. This research is conducted to explain and give an overview of the program as well as explore the support system of the program. Three primary data, namely a depth-interview, questionnaire, and documentation, are gathered to explore the SSE program. The participants are lectures, faculty management, and students involved in the SSE in 2018-2019. The existence of the SSE program was exceedingly influenced by the faculty participation in AUCPESS. A grant from the Dharmasiswa Scholarship that aimed to bolster the exchange of culture and build up the Faculty's International atmosphere was the first booster. However, after the funding stopped, the program ran independently with non-financial support from Rector, faculty management, partner universities, and students. Hence, funding is not a pivotal issue as long as the University and faculty management eager to support the program.